Trajnost vpisa v naravovarstvene kopop operacije HAB, MET, VTR in STE v programskih obdobjih 2007–2013, 2014–2020 in 2023–2027 - Žvikart, Mateja (Varstvo narave, 2025)
The durability of the implementation of modified agricultural practices is crucial for the long-term preservation and improvement of the status of endangered species and habitat types in the agricultural cultural landscape. Therefore, an analysis of the durability of entry into the target nature conservation operations KOPOP between individual programming periods was carried out. The results of the analysis of the last two programming periods show a high percentage of durability in VTR (75.6%) and HAB (70.1%) operations, while in MET operations this percentage is 44.5% and in STE operations only 24%. Due to the importance of long-term implementation of modified agricultural practices on areas that are habitats for endangered species and habitat types, it would be reasonable to introduce an additional payment for areas where such use is carried out over several programming periods.
Keywords: common agricultural policy; KOPOP; modified agricultural practice; prilagojena kmetijska praksa; skupna kmetijska politika